Về một phương pháp điều khiển cựu trị hội tụ nhanh - Mạnh, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
A very fast converging algorithm for extremal control systems is  presented in this paper. The algorithm is called “Cleftover stepping in sequentially stretched space”. The paper describes the  optimization algorithm as well as, a model of  extremal control systems and results of experimental computation.